2018
DOI: 10.1016/j.critrevonc.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

A question of class: Treatment options for patients with relapsed and/or refractory multiple myeloma

Abstract: A B S T R A C TMultiple classes of agent with distinct mechanisms of action are now available for the treatment of patients with relapsed and/or refractory multiple myeloma (RRMM), including immunomodulatory agents, proteasome inhibitors, histone deacetylase inhibitors and monoclonal antibodies. Additionally, several different drugs may be available within each agent class, each with their own specific efficacy and safety profile. This expansion of the treatment landscape has dramatically improved outcomes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…Only aggressive and prompt treatment can induce a rapid response of hematologic disease and reduce the organ damage caused by cryoglobulin. [ 22 24 ] In our patient, despite the prompt start of an integrated therapeutic approach with prostanoid infusion, [ 25 ] plasmapheresis, [ 23 , 26 ] and chemotherapy, [ 2 , 27 ] vascular damage was advanced and irreversible. Therefore, the patient was subjected to amputation of both feet because of necrosis.…”
Section: Discussionmentioning
confidence: 91%
“…Only aggressive and prompt treatment can induce a rapid response of hematologic disease and reduce the organ damage caused by cryoglobulin. [ 22 24 ] In our patient, despite the prompt start of an integrated therapeutic approach with prostanoid infusion, [ 25 ] plasmapheresis, [ 23 , 26 ] and chemotherapy, [ 2 , 27 ] vascular damage was advanced and irreversible. Therefore, the patient was subjected to amputation of both feet because of necrosis.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple myeloma (MM) is the third most common hematologic malignancy worldwide, characterized by excessive proliferation of monoclonal plasma cells 1,2 . The development of novel anti-MM agents has expanded treatment options for MM patients and improved outcomes 3 . Despite recent treatment advances, MM remains incurable, with most patients relapsing and developing treatment-refractory disease 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent treatment advances, MM remains incurable, with most patients relapsing and developing treatment-refractory disease 1 . Relapsed and refractory MM (RRMM) represents a challenging disease to treat, given the heterogeneity of the disease and patient population [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Different novel therapeutic agents that are usually given in various combinations are currently available for the treatment of patients with RR disease [61,62]. However, in the setting of RR disease, treatment options become more complex, but the aim should be to provide the patient with specific drug combination so as to gain clinical benefit while minimizing drug toxicity [63]. Additionally, studies have shown clinical benefit for continued therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the choice of therapeutic regimen should take disease-related factors and patientrelated factors into consideration [62,63,73].…”
Section: Introductionmentioning
confidence: 99%